A kind of nano hybrid aerogel and preparation method thereof

By combining polymer electrospinning fibers, graphene oxide and conductive polymers in nanohybrid aerogels, the problem of nanomaterial composite is solved, and the stable composite and conductivity of nanomaterials are achieved. It is suitable for wearable electronic products. multifunctional application.

CN116265076BActive Publication Date: 2025-02-21DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111547628.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-16
Publication Date
2025-02-21
Estimated Expiration
2041-12-16

AI Technical Summary

Technical Problem

Nanomaterials are difficult to recombine into the same system due to weak intermolecular forces, making it difficult to achieve effective recombination of multifunctional nanomaterials in wearable electronic products.

Method used

Using the preparation method of nanohybrid aerogel, by combining polymer electrospinning fibers, graphene oxide and conductive polymers, the self-assembly properties of graphene oxide promote the recombination of 1D and 2D nanomaterials and conduct electricity. Polymers connect the entire aerogel system to improve stability.

Benefits of technology

The stable composite of nanomaterials is achieved, and the conductivity of the aerogel is improved, so that it can be connected into the circuit as a conductor, light up the LED light, and display excellent compression performance and recovery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003416176900000011
    Figure HDA0003416176900000011
  • Figure HDA0003416176900000012
    Figure HDA0003416176900000012
  • Figure HDA0003416176900000021
    Figure HDA0003416176900000021
Patent Text Reader

Abstract

The invention discloses a nano hybrid aerogel and a preparation method thereof, belonging to the technical field of aerogel preparation. The components of the nano hybrid aerogel include: polymer electrostatic spinning fiber, graphene oxide and conductive polymer; the polymer electrostatic spinning fiber is selected from at least one of polyacrylonitrile electrostatic spinning fiber, polynylon 66 electrostatic spinning fiber and polypropylene fiber; the conductive polymer is selected from at least one of polyaniline, polypyrrole and polyethylene dioxythiophene. The invention utilizes the self-assembly characteristics of graphene oxide to solve the problem that nano materials are difficult to integrate into the same system due to weak interaction forces.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aerogel preparation, and particularly relates to a nano hybrid aerogel and a preparation method thereof. Background Art

[0002] Among various functional materials, 0D (zero-dimensional), 1D (one-dimensional) and 2D (two-dimensional) nanomaterials are often used in wearable electronic products due to their advantages such as large specific surface area, high aspect ratio, good conductivity and fast electron transmission speed. However, each nanomaterial generally has inherent advantages and disadvantages. For example, 0D Cu nanoparticles with excellent thermal conductivity are limited by their limited tendency to be oxidized. Silver nanowires (AgNWs), as a typical one-dimensional nanomaterial, have good conductivity, but they inevitably have node resistance between nanowires. Graphene is an ideal two-dimensional nanomaterial. Although it has excellent flexibility, it cannot be used in digital electronic devices because it has no band gap.

[0003] Based on this, there is an urgent need to prepare hybrid nanostructures composed of two or more nanomaterials to complement the inherent advantages and disadvantages of each nanomaterial. However, due to the weak molecular connection force of nanomaterials or the lack of effective mass transfer channels, it is still a huge challenge to combine multifunctional nanomaterials into the same system. Summary of the invention

[0004] The present invention provides a nano hybrid aerogel and a preparation method thereof, which solves the problem that nano materials are difficult to be compounded into the same system due to weak intermolecular forces.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] In one aspect of the present invention, a nano hybrid aerogel is provided, wherein the components of the nano hybrid aerogel include: polymer electrospun fibers, graphene oxide and a conductive polymer;

[0007] The polymer electrospun fiber is selected from at least one of polyacrylonitrile electrospun fiber, polynylon 66 electrospun fiber and polypropylene fiber;

[0008] The conductive polymer is selected from at least one of polyaniline, polypyrrole and polyethylenedioxythiophene.

[0009] Optionally, the mass ratio of the polymer electrospun fiber to the conductive polymer is 1:(0.1-0.5);

[0010] The mass ratio of the polymer electrospun fibers to the graphene oxide is 1:(1-5).

[0011] Optionally, the mass ratio of the polymer electrospun fiber and the conductive polymer is independently selected from 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, or any value between any two of the above points; the mass ratio of the polymer electrospun fiber and the graphene oxide aqueous dispersion can be independently selected from 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, or any value between any two of the above points.

[0012] Optionally, the degree of polymerization of the polymer electrospun fibers is 15,000 to 20,000.

[0013] Optionally, the degree of polymerization of the polymer electrospun fibers is independently selected from 15000, 16000, 17000, 18000, 20000, or any value between any two of the above points.

[0014] In another aspect, the present invention provides a method for preparing the above-mentioned nano-hybrid aerogel, comprising the following steps:

[0015] (1) adding the polymer electrospun into deionized water and dispersing it to obtain a nanofiber dispersion;

[0016] (2) preparing a hydrochloric acid aqueous solution containing a conductive polymer monomer, and stirring and mixing the aqueous solution with the nanofiber dispersion to obtain a mixed solution;

[0017] (3) adding an initiator to the mixed solution to undergo a polymerization reaction to obtain a polymer electrospun fiber loaded with a conductive polymer;

[0018] (4) mixing the polymer electrospun fibers loaded with the conductive polymer with the graphene aqueous dispersion to react and obtain a block product, and freeze-drying the block product to obtain the nano hybrid aerogel.

[0019] Optionally, in step (1), the dispersion speed is 8000-15000 rpm, and the dispersion time is 2-5 min;

[0020] The concentration of the nanofiber dispersion is 3 to 10 mg mL -1 .

[0021] Optionally, the upper limit of the dispersion speed is independently selected from 13000 rpm, 13500 rpm, 14000 rpm, 14500 rpm, 15000 rpm, and the lower limit is independently selected from 8000 rpm, 8500 rpm, 9000 rpm, 9500 rpm, 10000 rpm.

[0022] Optionally, the concentration of the nanodispersion is independently selected from 3 mg mL -1 , 5mg mL-1 , 7mg mL -1 , 8mg mL -1 , 9mgmL -1 , or any value between any two of the above points.

[0023] Optionally, in step (2), the conductive polymer monomer is selected from at least one of aniline, polypyrrole, and polyethylenedioxythiophene;

[0024] The hydrochloric acid concentration in the hydrochloric acid aqueous solution is 0.5 to 5 mol L -1 ;

[0025] Optionally, the upper limit of the hydrochloric acid concentration in the hydrochloric acid aqueous solution is independently selected from 3 mol L -1 , 3.5 mol L -1 , 4 mol L -1 , 4.5 mol L -1 , 5 mol L -1 , the lower limit is independently selected from 0.5 mol L -1 , 1 mol L -1 , 1.5 mol L -1 , 2 mol L -1 , 2.5 mol L -1 .

[0026] The stirring and mixing temperature is 0 to 5° C.; the stirring and mixing time is 0.5 to 3 hours.

[0027] Optionally, the stirring and mixing temperature is independently selected from 0.5°C, 1°C, 2°C, 3°C, 4.5°C, or any value between any two of the above points; the stirring and mixing time is independently selected from 0.8h, 1h, 1.5h, 2h, 2.5h, or any value between any two of the above points.

[0028] Optionally, in step (3), the initiator is ammonium persulfate; the amount of the ammonium persulfate is 1% to 20% of the mass of the conductive polymer monomer;

[0029] The polymerization reaction temperature is 0-5°C; the polymerization reaction time is 0.5-4h.

[0030] Optionally, the upper limit of the amount of ammonium persulfate is independently selected from 18%, 18.5%, 19%, 19.5%, 20%, and the lower limit is independently selected from 1%, 1.5%, 2%, 2.5%, 3%.

[0031] Optionally, the temperature of the polymerization reaction is independently selected from 0.5°C, 1°C, 2°C, 3°C, 4.5°C, or any value between any two of the above points; the temperature of the polymerization reaction is independently selected from 0.8h, 1h, 2h, 3h, 3.5h, or any value between any two of the above points.

[0032] Optionally, in step (4), the reaction temperature of the reaction is 100 to 150° C.; the reaction time of the reaction is 12 to 48 hours.

[0033] Optionally, the upper limit of the reaction temperature is independently selected from 130°C, 135°C, 140°C, 145°C, and the lower limit is independently selected from 105°C, 110°C, 115°C, 120°C, 125°C.

[0034] Optionally, the reaction time is independently selected from 15 h, 18 h, 20 h, 24 h, 28 h, 30 h, 35 h, 36 h, 40 h, 45 h, or any value between any two of the above points.

[0035] Optionally, in step (4), the freeze-drying temperature is -60 to -70°C and the time is 24 to 72 hours.

[0036] As an embodiment of the present invention, a method for preparing a nano-hybrid aerogel is proposed, comprising:

[0037] The polymer electrospun is added to deionized water and dispersed using a high-speed disperser to prepare a nanofiber dispersion;

[0038] Adding the conductive polymer monomer into the hydrochloric acid aqueous solution and stirring and mixing with the nanofiber dispersion;

[0039] adding an initiator into the mixed solution, loading the conductive polymer on the polymer electrospun fiber through a polymerization reaction, and obtaining a conductive polymer / polymer electrospun fiber;

[0040] The graphene aqueous dispersion is mixed with the conductive polymer / polymer electrospun fiber, and the mixture is transferred to a high-pressure reactor for high-temperature reaction to obtain a bulk product;

[0041] The block product is freeze-dried to obtain the product nano-hybrid aerogel.

[0042] The beneficial effects of the present invention include:

[0043] 1. The present invention promotes the composite of 1D and 2D nanomaterials by utilizing the self-assembly characteristics of graphene oxide, thereby solving the problem that nanomaterials are difficult to composite into the same system due to weak intermolecular forces.

[0044] 2. The conductive polymer prepared in the present invention acts as a "bridge" between the nanofibers and graphene oxide, making the entire aerogel system more stable.

[0045] 3. The present invention introduces conductive polymers to make the aerogel have good conductivity, and can be connected to the circuit as a conductor to light up the LED lamp. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 The SEM images of AH-1 aerogel at different resolutions;

[0047] Figure 2 Cyclic compression stress-strain curves of AH-1 and AH-2 aerogels;

[0048] Figure 3 A design diagram of AH-1 aerogel used as a conductor to connect to a circuit;

[0049] Figure 4 This is a real picture of how AH-1 aerogel makes the LED light produce different brightness under different pressures. DETAILED DESCRIPTION

[0050] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0051] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0052] The polyacrylonitrile used in the embodiments of the present invention is produced by Aladdin Reagent (Shanghai) Co., Ltd., with a degree of polymerization of 15,000; the aniline is produced by Aladdin Reagent (Shanghai) Co., Ltd., with a purity of 99.5%; the graphene oxide aqueous dispersion comes from the Shanxi Coal Chemistry Institute of the Chinese Academy of Sciences.

[0053] Example 1

[0054] Preparation of PAN electrospun nanofibers and alkalized PAN (aPAN) nanofibers: Polyacrylonitrile powder (MW 15,000) was dissolved in N,N-dimethylformamide and stirred at 40 °C for 6 h to prepare an electrospinning solution with a PANI content of 10 wt%. Under the condition of applying a voltage of 20 kV, 1 mL h -1The electrospinning process was carried out at a jet speed of , and the distance between the needle and the collecting plate was 18 cm. The aluminum foil on the stainless steel substrate was used as the substrate for the electrospun fiber membrane. The PAN nanofibers obtained by spinning were placed in an oven at 60°C and dried for 1 hour, and then transferred to a 1M NaOH aqueous solution for treatment for 3 hours. The resulting product was then washed with deionized water several times until the pH of the supernatant became neutral. The final product was placed in an oven at 60°C and dried for 48 hours to obtain an alkaline-treated PAN nanofiber membrane, which was recorded as aPAN.

[0055] Example 2

[0056] The aPAN nanofiber membrane obtained in Example 1 was cut into small pieces, transferred into deionized water, and dispersed using a high-speed disperser at a speed of 10000 rpm to prepare a nanofiber dispersion (10 mg mL -1 ). Aniline was added to 50 mL of 1 M HCl aqueous solution and stirred with the nanofiber dispersion for 30 min (the mass ratio of aniline to nanofibers was 2:1). Then ammonium persulfate was added (the mass ratio of ammonium persulfate to aniline was 1.25:1), and the polyaniline fibers were loaded on the aPAN nanofibers through polymerization. After the above polymerization process was carried out at 0 ° C for 4 h, the composite was repeatedly washed with deionized water to remove impurities. Next, the GO dispersion (10 mg mL -1 ) was mixed with the composite (the mass ratio of GO to aPAN was 1:1), and the mixture was transferred to an autoclave and reacted at 120°C for 24 hours. After the reaction, the autoclave was cooled to room temperature to obtain a block product, which was finally freeze-dried for 24 hours to obtain the product aerogel, denoted as AH-1. Its SEM images at different resolutions are shown in the following figure. Figure 1 shown.

[0057] Example 3

[0058] The aPAN nanofiber membrane obtained in Example 1 was cut into small pieces, transferred into deionized water, and dispersed using a high-speed disperser at a speed of 80,000 rpm to prepare a nanofiber dispersion (5 mg mL -1 ). Aniline was added to 50 mL of 2M HCl aqueous solution and stirred with the nanofiber dispersion for 30 min (the mass ratio of aniline to nanofibers was 2:1). Then ammonium persulfate was added (the mass ratio of ammonium persulfate to aniline was 1.25:1), and the polyaniline fibers were loaded on the aPAN nanofibers through polymerization. After the above polymerization process was carried out at 4 °C for 4 h, the composite was repeatedly washed with deionized water to remove impurities. Next, the GO dispersion (10 mg mL -1) was mixed with the composite (the mass ratio of GO to aPAN was 1:1), and the mixture was transferred to an autoclave and reacted at 120°C for 24 hours. After the reaction, the autoclave was cooled to room temperature to obtain a block product, which was finally freeze-dried for 48 hours to obtain the product aerogel, recorded as AH-2.

[0059] Test Case

[0060] The aerogel samples prepared in Examples 2 to 3 were subjected to compression performance tests on an Instron universal testing machine, with the compression speed set at 2 mm / min. After the test, the corresponding compression load-displacement data were derived and converted into a compression stress-strain curve using a formula. The formula for converting displacement data into compression strain data in the compression test is: where ε c represents the compressive strain, l c represents the displacement of the sample block, and h represents the original thickness of the sample block. The formula for converting the compressive load into compressive stress data is: where σ c represents the compressive stress, F c represents the compressive load, and S represents the bottom area of ​​the cylindrical specimen.

[0061] Specific test results are as follows Figure 2 As shown in the figure, it can be seen that both AH-1 aerogel and AH-2 aerogel show great recovery after four consecutive compression processes. Under the same compression strain conditions, AH-1 has better compression performance than AH-2.

[0062] The aerogel sample prepared in Example 2 is connected to a circuit (circuit design diagram as shown in FIG. Figure 3 As shown), the LED light can be turned on. Figure 3 As shown in the figure, AH-1 aerogel can make LED lamps have different brightness under different pressures. The brightness of AH-1 aerogel increases with the increase of pressure (0.79, 0.88, 1.13, 1.59, 2.21, 2.83 kPa).

[0063] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A nano hybrid aerogel, characterized in that: The components of the nano hybrid aerogel include: polymer electrospun fibers, graphene oxide and conductive polymer; The polymer electrospun fiber is selected from at least one of polyacrylonitrile electrospun fiber, polynylon 66 electrospun fiber and polypropylene fiber; The conductive polymer is selected from at least one of polyaniline, polypyrrole and polyethylenedioxythiophene; The nano hybrid aerogel is obtained by the following steps: (1) adding polymer electrospun fibers into water and dispersing them to obtain nanofiber dispersion; (2) preparing a hydrochloric acid aqueous solution containing a conductive polymer monomer, and stirring and mixing the aqueous solution with the nanofiber dispersion to obtain a mixed solution; (3) adding an initiator to the mixed solution to undergo a polymerization reaction to obtain a polymer electrospun fiber loaded with a conductive polymer; (4) mixing the polymer electrospun fiber loaded with the conductive polymer with the graphene aqueous dispersion, reacting, and freeze-drying to obtain the nano hybrid aerogel; The degree of polymerization of the polymer electrostatic spinning fiber is 15000-20000.

2. The nano-hybrid aerogel according to claim 1, characterized in that: The mass ratio of the polymer electrospun fiber to the conductive polymer is 1:(0.1-0.5); The mass ratio of the polymer electrospun fibers to the graphene oxide is 1:(1-5).

3. The nano-hybrid aerogel according to claim 1, characterized in that: In step (1), the dispersion speed is 8000-15000 rpm, and the dispersion time is 2-5 min; The concentration of the nanofiber dispersion is 3 to 10 mg mL -1 .

4. The nano-hybrid aerogel according to claim 1, characterized in that: In step (2), the conductive polymer monomer is selected from at least one of aniline, polypyrrole, and polyethylenedioxythiophene; The hydrochloric acid concentration in the hydrochloric acid aqueous solution is 0.5 to 5 mol L -1 ; The stirring and mixing temperature is 0 to 5° C.; the stirring and mixing time is 0.5 to 3 hours.

5. The nano-hybrid aerogel according to claim 1, characterized in that: In step (3), the initiator is ammonium persulfate; the amount of the ammonium persulfate is 1% to 20% of the mass of the conductive polymer monomer; The polymerization reaction temperature is 0-5°C; the polymerization reaction time is 0.5-4h.

6. The nano-hybrid aerogel according to claim 1, characterized in that: In step (4), the reaction temperature of the reaction is 100 to 150° C.; the reaction time of the reaction is 12 to 48 hours.

7. The nano-hybrid aerogel according to claim 1, characterized in that: In step (4), the freeze-drying temperature is -60 to -70°C and the time is 24 to 72 hours.